TANBUR: ONE OF ANCIENT INSTRUMENTS - Muyassarxon Achildiyeva; Nazokatxon Axmedova; Farangiz Ikromova; Oygulxon Haydarova; Gulsoraxon Ibrahimova; Akromjon Abdurahmonov (Galaxy International Interdisciplinary Research Journal, 2021)
This article gives information about the origin of the word 7tanbur, which is one of the ancient instruments, and its stages of development. It also discusses the current significance of the Khorezm tanbur line, the process of historical and theoretical development.